Low serum zinc and short stature in children - Kadek Wini Mardewi; I Gusti Lanang Sidiartha; Eka Gunawijaya (Indonesian Pediatric Society, 2016)
Background Short stature/stunting is common in developing countries, and has been used as an indicator of a nationâ€™s general health condition. Short stature increases the risk of metabolic disease, disturbances in cognitive development, infection prevalence, physical as well as functional deficits, and even death. Nutritional factors that frequently cause stunting are low intake of energy, protein, or micronutrients such as iron, vitamin A, and zinc. The role of zinc supplementation in children with short stature has not been well defined. In addition, zinc supplementation should be evaluated in the setting of specific conditions and regions.Objective To assess the association between low serum zinc level and short stature in children.Methods This cross-sectional study was done in a primary health care center at Klungkung I, Klungkung District, from August to September 2013. Children with short and normal stature (as reference group) were enrolled and their serum zinc level was measured, Other risk factors were inquired by questionnaire. Association between low serum zinc level (<65 Âµg/dL) and short stature was analyzed by stepwise multivariable regression analysis; degree of association was presented as odds ratio (OR) and its corresponding confidence interval.Results The prevalence of low serum zinc level in our subjects was 71%. Low serum zinc level was significantly associated with short stature [adjusted OR 16.1; 95%CI 3.1 to 84.0; (P=0.001)]. In addition, the occurrence of low serum zinc was higher in the short stature group (88.5%) compared to the normal stature group (53.8%). We also found that low calorie intake was associated with short stature [adjusted OR 29.4; 95%CI 2.76 to 314.7; (P=0.001)].Conclusion Low serum zinc level appears to be associated with short stature. [Paediatr Indones. 2016;56:171-5.].